ALUMINUM-CHLORIDE CATALYZED STEREOSPECIFIC AND REGIOSPECIFIC ALLYLSILYLATION OF ALKYNES - A CONVENIENT ROUTE TO SILYLDIENES - YEON, SH; HAN, JS; HONG, E; DO, Y; JUNG, IN (ELSEVIER SCIENCE SA LAUSANNE, 1995)
Allyltrimethylsilane reacts with phenylalkynes in the presence of aluminum chloride catalyst under mild conditions to afford silylphenyldienes in moderate yield. In this allylsilylation reaction, the silyl group adds regioselectively to the terminal carbon and the allyl group to the inner carbon of the triple bond. The allylsilylation of phenylacetylene gives the allylsilylated product having the silyl and allyl groups in the cis-position, while diphenylacetylene gives the trans product. The allylic inversion was also observed in the allylsilylation with the stereohomogeneous (Z)-crotyltrimethylsilane. These results are consistent with the initial formation of trimethylsilyl cation intermediate and a stepwise process of allylsilylation.
Keywords: AROMATIC-SUBSTITUTION; CATIONS; STABILIZATION; DERIVATIVES; COMPLEXES; MAGNITUDE